Der digitale Pranger Bewertungsportale im Internet - Franz, Ulrich (Schriftenreihe der Juristischen Gesellschaft zu Berlin, 2018)
As a source of information for consumers to assess the quality of goods and services, rating portals basically make a useful contribution to consumer protection. However, the portals become a problem when critics express existence-destroying criticism out of the protection of anonymity. The legal possibilities for those affected to defend themselves against unjustified criticism are presented. The highly topical question of how those affected can take legal action against unjustified criticism on a rating portal that is permanently accessible to an unlimited circle of users and can be quickly found by search engines is dealt with.